2010
DOI: 10.1007/s12105-010-0216-0
|View full text |Cite
|
Sign up to set email alerts
|

Odontogenic Epithelium: Immunolabeling of Ki-67, EGFR and Survivin in Pericoronal Follicles, Dentigerous Cysts and Keratocystic Odontogenic Tumors

Abstract: The aim of this study was to evaluate the biological profile of odontogenic epithelium by immunolabeling of epidermal growth factor receptor (EGFR), Ki-67 and survivin in keratocystic odontogenic tumors (KOT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 36 publications
6
33
0
3
Order By: Relevance
“…Presented study also revealed that strong cytoplasmic and nuclear survivin staining in stromal cells was in CAs and KCOTs, but weak staining in DCs and RCs. In the article of de Oliveira et al (27), survivin staining patterns in DCs and KCOTs is also similar to our observations. Furthermore, some authors hypothesized that cytoplasmic survivin expression is responsible for poor prognosis and for the resistance to therapy in oral squamous cell carcinoma (31).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Presented study also revealed that strong cytoplasmic and nuclear survivin staining in stromal cells was in CAs and KCOTs, but weak staining in DCs and RCs. In the article of de Oliveira et al (27), survivin staining patterns in DCs and KCOTs is also similar to our observations. Furthermore, some authors hypothesized that cytoplasmic survivin expression is responsible for poor prognosis and for the resistance to therapy in oral squamous cell carcinoma (31).…”
Section: Discussionsupporting
confidence: 92%
“…Although there are several studies related to role of these proteins in odontogenic lesions in English literature (8,9,18,24,(27)(28)(29), no comparative and comprehensive study, in which the expression of these proteins or adhesion molecules in odontogenic cystic lesions have been evaluated, to our knowledge. Therefore, we aim to evaluate the immunohistochemical expressions of CD138 (syndecan-1), CD38, E-cadherin and survivin in these cystic odontogenic lesions and investigate the potential implications of their expressions among these lesions.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study confirm previously published data on survivin expression in KCOTs (Andric et al, 2010; De Oliveira et al, 2011;Leonardi et al, 2013). The study also demonstrated that survivin immunostaining is a feature of the basal and parabasal epithelial layers of KCOTs.…”
Section: Discussionsupporting
confidence: 92%
“…It is hypothesized that survivin expression is correlated with high proliferative activity in the epithelium of KCOTs as well as apoptosis inhibition (Andric et al, 2010;De Oliveira et al, 2011). Similarly, cyclin D1, a protein which regulates the transition from G1 to S phase of the cell cycle, is also expressed in KCOTs (Kimi et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Epithelial cells in KCOTs seem to have a different proliferative potential from those of other odontogenic lesions 4.…”
Section: Discussionmentioning
confidence: 92%